Endogenous growth and cycles with a continuum of technologies - Ryo Horii (Osaka University, Institute of Social and Economic Research (ISER), 2001)
When a continuum of technologies is introduced to the model of Grossman and Helpman (1991), both continuous and discrete technological progress may occur as a result of technology choices by private firms. A good is created through R&D based on one of a continuum of technologies that differ in productivity, and the R&D cost is smaller when there is greater public knowledge about that technology, which accumulates through spillovers. When firms shift continuously to superior technologies, there is no incentive to retain existing technologies and the economy grows smoothly. By contrast, when many firms choose the same technology, accumulated knowledge makes this choice privately optimal for a certain time period, and the economy grows cyclically through a sequence of discrete progresses in technology. These two dynamics constitute multiple equilibria, and it depends on the size of the parameters which equilibrium is desirable for consumers.
Keywords: E32; O33; O41; 330; endogenous growth; growth cycles; technology choice; R&D spillovers; continuous and discrete technological progress; general purpose technologies; Neue Wachstumstheorie; Technologiewahl; Spillover-Effekt; Theorie